Studies on the Fluvial Environment, ARctic Coastal Plain Province, Northern Alaska. Volume I. - Lewellen,Robert I. (1972)
The studies on the fluvial environment of the Arctic Coastal Plain Province, Northern Alaska, include research which ranges in magnitude from small polygon troughs to the Inaru River Basin. The 208 figures include stereograms, ground and aerial photographs, graphs, curves, and maps. Ninety tables appear in the publication. The complete hydrographs for two tundra streams are included. Discussions include soil subsidence, soil consolidation, details of specific study sites and the findings, and a section on the Late Pleistocene and Recent. Instrumentation, methods, and the uses of aerial photography are included. Over 240 bibliographic entries provide references and a foundation for future research. Chronologies of physical events which occurred in the drainage basins are listed. The basic statistics and reproductions of computer printouts of the microclimatic data are presented in the Appendices. (Author( See also Volume 2, AD-749 151.